2017
DOI: 10.1101/149096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of mutational processes and selection on driver mutations across cancer types

Abstract: Epidemiological evidence has long associated environmental mutagens with increased cancer risk. However, links between specific mutation-causing processes and the acquisition of individual driver mutations have remained obscure. Here we have used public cancer sequencing data to infer the independent effects of mutation and selection on driver mutation complement. First, we detect associations between a range of mutational processes, including those linked to smoking, ageing, APOBEC and DNA mismatch repair (MM… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…A pilot study was conducted to compare the stability of signatures among different number of minimum SNVs (24, 48, 72 and 96, data not shown), and found that a cut point of 24 is sufficient. This is consistent with recent finding that 20 mutations gave an average classification accuracy of 80% across signatures . Any sample containing at least 24 SNVs was included for downstream assessment in order to enlarge the sample size as much as possible.…”
Section: Methodssupporting
confidence: 86%
“…A pilot study was conducted to compare the stability of signatures among different number of minimum SNVs (24, 48, 72 and 96, data not shown), and found that a cut point of 24 is sufficient. This is consistent with recent finding that 20 mutations gave an average classification accuracy of 80% across signatures . Any sample containing at least 24 SNVs was included for downstream assessment in order to enlarge the sample size as much as possible.…”
Section: Methodssupporting
confidence: 86%
“…Of interest, signatures 20 and 26, have been associated with defective MMR (Helleday, Eshtad, & Nik‐Zainal, ; Temko, Tomlinson, Severini, Schuster‐Bockler, & Graham, ; Wellcome Sanger Institute, ), but were not observed in the Lynch‐related sebaceous skin lesions in this study. Only three MMR‐deficient sebaceous lesions were tested in this study and so they may not represent the complete heterogeneity of mutation signatures that are observed in Lynch‐related sebaceous neoplasia.…”
Section: Discussionmentioning
confidence: 56%
“…The application of evolutionary theory allows us to infer cell growth dynamics, the number of driver alterations 17,18 and their selective fitness coefficients [19][20][21][22] , as well as the impact of deleterious mutations during cancer progression 23,24 . An evolutionary metric recently used to detect selection in cancer studies is the ratio of nonsynonymous to synonymous mutations, dN/dS 7,8,[25][26][27] .…”
Section: Introductionmentioning
confidence: 99%